Self-built field induces surface electrons to reduce H+ to atomic H* for photocatalytic hydrodechlorination of 2-chlorophenols - Bo Tang (Elsevier, 2021)
2-chlorophenols (2-CPs) as a biodegradation-resistant pollutant has serious threats to environment and human health. Photocatalytic hydrodechlorination (PHDC) for removal of halogenated organics in water has attracted more attention, however, low utilization-efficiency of atomic H* limits its application. Here, a platinum-load tungsten phosphide/graphitic carbon nitride photocatalyst (Pt-WP/g-C3N4) with enhanced activity for conversion of 2-CPs to biodegradable phenol is designed via prior density-functional-theory (DFT) simulations. Conversion yield of phenol on Pt-WP/g-C3N4 is 92.0%, which is far higher than that of Pt-g-C3N4 (17.8%). Self-built field among Pt, WP and g-C3N4 induces photo-generated electrons migration to reduce H+, while g-C3N4 acts as a ‘H-atom lagoons’ to store H*. Electron spin-resonance spectroscopy indicates that coupling of WP and Pt-g-C3N4 promotes H* production and utilization. Ab-initio molecular-dynamics simulations show that Pt-W-P interface has a good resistance to deactivation to enhance H* generation. It provides a deep understanding of PHDC mechanism and a feasible way to optimize decontamination on heterojunction photocatalyst.